Determinants and Impact of Foreign Institutional Investors: An Indian Perspective. - Jain, Puneet (2007)
Growth of Indian economy is a bit shy of 9% mark. The latter is a rough guide which the foreign investors reckon with, before committing large sums of money for investment. India is one of the biggest and fastest growing developing economies and has attracted the most investor attention in recent years. After liberalization of the Indian economy in 1991, it has become one of the hotspots for global investment. Foreign investment (both Foreign Direct Investment and Foreign Institutional Investment) helped to boost India's economic growth and transformed several sectors of the Indian Industry into globally competitive entities India is also the world's second fastest growing economy and boasts of highly competitive private companies, a booming stock market, and a modern, well-disciplined financial sector. The Indian stock markets witnessed unprecedented buoyancy during 2006-07 (Dalal Street, 2006). Strong macro-economic fundamentals, positive investment climate and sound business outlook drove the bullish trend. The results show that the industry has recorded a robust growth during this time period and has created great opportunities for investment. Further, the research compares India with four other leading developing countries (Brazil, Russia, China and South Africa) during 2006-07 and concludes that India is one of the fastest rising stars among all these major emerging economies with its economic growth rate running at over 9% annually.(Economic Times, Feb 2007). In order to tap the true potential of the economy, the Indian Government and financial community need to be pro-active in promoting the country as a safe destination for foreign capital, while at the same time ensuring that the vital interests of the economy are not adversely affected.